Antihydrogen formation by autoresonant excitation of antiproton plasmas - Michael Charlton (Hyperfine Interactions, 2012)
One of a series of conference papers (presented at the Vancouver LEAP meeting) giving more detailed descriptions of aspects of the ALPHA/Swansea work on positrons and antihydrogen.